Another one bites the dust? A critical appraisal of the new draft of the Nordic Saami convention from the perspective of indigenous rights - Vidmar, Lana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The Nordic Saami Convention is a proposed agreement between Norway, Sweden and Finland that will create the legal framework for the protection of the Saami peoples' rights. Saami parliaments and communities expressed their disagreement with the initial text. The article analyses the Draft of the Nordic Saami Convention from the perspective of protection of indigenous rights. The methodology used is desk analysis of the scientific literature and policy documents. The provisions given in the Draft are compared against documents concerning indigenous and Saami rights. Particular attention is paid to land rights, the right to self-determination, traditional occupations and language. The analysis shows that the Draft does not acknowledge the indigenous rights of the Saami people to the fullest, nor the specific cultural, economic, historic or linguistic context of the Saami.
Keywords: domorodna ljudstva; pravno varstvo; Samiji; Nordijska konvencija o Samijih; Norveška; Švedska; Finska; mölkky